The Use of Lupin Flour to produce food by extrusion cooking - Mohammed, Zeinab Haron; Boskaya, Mohamed H. (Al-Mukhtar Journal of Sciences, 2003)
Lupinus luteus flour, was processed using a Clextral Bc21 Twin Screw Extruder. It was not easy to obtain a continuous homogeneous product from lupin flour. The lupin extruate was not texturised, showed little expansion at the die and no decrease in protein solubility in 1% sodium dodecyl sulphate (SDS) solution as a result as extrusion. Extrusion processing under the conditions used here did not alter the lupin alkaloid content. It was concluded that the extrusion behavior was a consequence of the lower viscosity of the lupin (melt). This was shown by the lower extruder torque and pressure and was probably a consequence of the lubricating affect of the higher level of fat in the lupin flour.